Neurocognitive and cerebellar function in ADHD, autism and spinocerebellar ataxia - Cundari, Maurizio; Vestberg, Susanna; Gustafsson, Peik; Gorcenco, Sorina; Rasmussen, Anders (Frontiers in Systems Neuroscience, 2023)
The cerebellum plays a major role in s balance, motor control and sensorimotor integration, but also cognition, language, and emotional regulation. Several neuropsychiatric disorders such as attention deficit-hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and various neurological diseases such as spinocerebellar ataxia type 3 (SCA3) are associated with deficits in cerebellar function. Morphological abnormalities in different cerebellar subregions produce distinct behavioral symptoms related to the functional disruption of specific cerebro-cerebellar circuits. The specific contribution of the cerebellum to typical development may therefore involve the optimization of the structure and function of cerebro-cerebellar circuits underlying skill acquisition in multiple domains. Here, we review cerebellar structural and functional differences between healthy subjects and patients with ADHD, ASD, and SCA3. How does disruption of these cerebellar networks affect cognitive functions and their associated neurocognitive functions in ADHD, ASD, and SCA3? We discuss how cerebellar computations contribute to performance on cognitive and motor tasks and how cerebellar signals are interfaced with signals from other brain regions during normal and pathological behavior. We conclude that although there is little doubt that the cerebellum plays a role in many cognitive functions, more studies are needed to clarify the cerebellum's role in normal and pathological behavior and cognitive functioning.